The Effect of Peer Group Influence and the Role of Parents on Adolescent Behaviors - Gina Tomé , Margarida Gaspar de Matos, Inês Camacho, Celeste Simões, José Alves Diniz (Pakistan Journal of Psychology, 2012)
The purpose of this study is to analyze the influence of peer groups on adolescent risk and health behaviors. The study will examine whether adolescents who have more friends engaging in risk behaviors adopt more risk behaviors and if those whose friends engage in protective behaviors, have higher welfare. If this trend is found, we will try to understand whether parental monitoring will somewhat moderate this influence. The sample was composed by individuals that participated in the study in continental Portugal, integrating the European study HBSC – Health Behaviour in School-aged Children. The study included a total of 4877 students from the 6th, 8th and 10th grades from Portuguese public schools, with an average age of 14 years. The results revealed the influence of peer group can be negative when they have more risk behaviors and positive when they have more protective behaviours. Parental monitoring is important for risk behaviors and welfare and influences happiness and life satisfaction of adolescents, but does not moderate the influence of peers